Autonomy of nurse profession in the awareness of nurses taking into account their professional functions - Glińska, Jolanta; Lewandowska, Małgorzata (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Introduction. Contemporary nursing widens the scope of competences and independence of a nurse. It means getting away from passivity in favour of multidirectional activity, aiming at performing autonomic actions concentrated on the subject of care. Nowadays, a nurse plays a role of a therapist, a source and a coordinator by performing her professional functions. This essential change in a role of a nurse allows more appropriately respond to the needs and expectations of the patient. Aim. The aim of this work was to find the answers to the following questions: what is the level of nurses« knowledge on a contemporary role of a nurse? Which professional functions do nurses hold and which factors appearing in the workplace influence the implementation of contemporary nurse duties? Material and methods. The research group consisted of 114 nurses. The data was collected on the basis of the self-made questionnaire. The variable was analyzed with the help of Pearson’s chi-square test (χ2). Results and conclusions. Presented research shows that there is a connection between implementation of professional functions and the attitude of coworkers. Obtained results show that the knowledge of nurses on their contemporary professional role is not satisfactory.